A soil fungal metacommunity perspective reveals stronger and more localised interactions above the tree line of an alpine/subalpine ecotone. (August 2019) - Beck, Sarah; Anderson, Ian C.; Drigo, Barbara; Powell, Jeff R.
Abstract: Dispersal affects community structure by facilitating colonisation and homogenising local communities, while species sorting along environmental gradients contributes to divergent community assembly. Fungi often have widespread distributions and are assumed to be dispersed easily across the landscape, with environmental selection being a primary driver of community assembly. To investigate the influence of spatial and environmental characteristics in shaping fungal community patterns, we characterised 143 communities of soil fungi along an altitudinal transect in Australia transitioning from subalpine to alpine vegetation (approximately 150 m difference in elevation over a distance of 1200 m). First, we inferred drivers of community assembly using canonical analyses including climate, edaphic properties, vegetation and spatial variables, all of which explained a statistically significant but very small amount of variation. We then employed an approach that defines the metacommunity with which each local community interacts via immigration and emigration and then estimates metacommunity characteristics. Using this approach, we inferred scales over which community interactions occurred along spatial, environmental and phylogenetic dimensions and the strength of community interactions based on the similarity of local communities to the metacommunity. Constructed metacommunities above the tree line consisted of local communities that were more clustered in space and more homogeneous than those at or below the tree line. Thus, mixing is likely occurring to a greater degree among fewer communities in the alpine environment. Comparisons of metacommunity estimates suggested that fungal evolutionary histories did not constrain community assembly as strongly as spatial proximity or environmental variation. This work suggests that differences exist in how fungal communities assembly along this altitudinal transect, despite site on its own explaining little compositional variation, and that the rate and the degree of species mixing among communities differs depending on the environmental context. Highlights: We studied 143 soil fungal communities along a subalpine/alpine ecotone. Climate, vegetation, soil and space explained very little variation. Metacommunity extent and strength of community interactions were estimated. Greater mixing among fewer communities was observed above the tree line. Mixing occurred over greater distances but with more divergence below the tree line.